(untitled) (American Journal of Human Psychology, 2024)
Anxiety disorders, including generalized anxiety disorder (GAD), social anxiety disorder (SAD), panic disorder, and specific phobias, are significant public health concerns that affect millions worldwide and lead to substantial impairments in daily functioning and quality of life. Traditional treatments may not suit everyone, highlighting the need for alternatives like Mindfulness-Based Stress Reduction (MBSR), which emphasizes mindfulness meditation. This systematic review evaluates the effectiveness of MBSR in reducing anxiety symptoms across various anxiety disorders by synthesizing research findings from studies published between January 2013 and April 2024. A comprehensive search was conducted in electronic databases, including PubMed, Semantic Scholar, ScienceDirect, PsycINFO, and Web of Science, using keywords such as “Mindfulness-Based Stress Reduction,” “MBSR,” “anxiety disorder,” and “effectiveness.” Peer-reviewed studies assessing the efficacy of MBSR on anxiety disorders were included, with data extraction and quality assessment performed following PRISMA 2022 guidelines. The search identified 1095 articles, with 13 studies meeting the inclusion criteria for the final analysis, encompassing a total sample size of 751 participants. The studies varied in design, sample size, participant demographics, and targeted anxiety disorders. Findings consistently showed significant reductions in anxiety symptoms among participants receiving MBSR compared to control groups. For GAD, studies reported improvements in anxiety and stress measures such as the Beck Anxiety Inventory (BAI) and Hamilton Anxiety Rating Scale (HAM-A). For SAD, reductions in social anxiety symptoms were observed, with some studies showing comparable effectiveness to CBT. This review presents compelling evidence supporting the efficacy of MBSR in reducing symptoms associated with anxiety disorders. Future research should focus on the long-term effects, impact on diverse demographic groups, and specific mechanisms to improve its clinical applicability.